The Habituation of Islamic Values Through Children’s Daily Activities at Tadika Al Fikh Orchard Johan Setia - Muhammad Rosyad Cahyadi; Rizka Harfiani (Al-Ulum: Jurnal Pendidikan Islam, 2026)
The limited implementation of structured Islamic value habituation in early childhood education hinders the optimal development of children’s religious character. This study examines the implementation of Islamic value habituation at Tadika Al Fikh Orchard Johan Setia using a qualitative descriptive approach. Data were collected through observation, interviews, and documentation, and analyzed using an interactive analysis model with triangulation for validity. The findings show that Islamic values are habituated through routine activities such as greetings, prayers, hygiene, and polite behavior, supported by teachers’ role modeling. Challenges include differences in home practices, children’s limited focus, and uneven parental support. Overall, Islamic value habituation contributes positively to the development of children’s religious attitudes, discipline, morals, and social awareness.